The characteristics of patients’ medical care, living will, and signs of death by age and the place of death: A cross-sectional study using a questionnaire survey targeting physicians with expertise in end-of-life care - Mitsutaka Yakabe; Tatsuya Hosoi; Shoya Matsumoto; Shoho Miura; Kazuhiro Hoshi; Soichiro Iwao; Yoshihiro Kitamura; Masahiro Akishita; Sumito Ogawa (PLoS ONE, 2026)
Objectives Few studies have examined how age and place of death among end-of-life patients are associated with the medical care they receive and the signs of death. Therefore, we aimed to clarify the characteristics of medical care, the implementation of living wills, and the signs of death in end-of-life patients by administering a self-developed questionnaire to physicians with expertise in end-of-life care. Methods Data were obtained through a web-based questionnaire administered to physicians registered with the Japan Society For Dying With Dignity. Each physician was asked to share data on a patient they had cared for, such as age, sex, place of death, presence of medical procedures and a living will, and signs of death. Results In total, 437 patients, aged 79.4 ± 15.3 years, were analyzed. Pain control and palliative care were provided to 225 and 278 patients, respectively. Moreover, 172 patients possessed a living will. After adjusting for factors using logistic regression analysis, the odds ratios (ORs) for pain control and palliative care were significantly lower in the older age groups. The OR for pain control in nursing homes, compared with home, was 0.305 [95% confidence interval (CI), 0.081–0.920], and the OR for palliative care was 0.212 [95% CI, 0.073–0.544]. The ORs of living wills were significantly lower in patients aged ≥90 years (0.401 [95% CI, 0.199–0.800]) than in those aged 20–64 and in hospitals (0.494 [95% CI, 0.294–0.815]) than at home. Factor analysis of 18 signs of death identified three factors. Factor 1 reflected global terminal decline, and receipt of palliative care was significantly associated with the signs loading on factor 1. Conclusion Provision of pain control, palliative care, and living wills differed by age group and place of death. Our findings suggest priorities for end-of-life care across settings and for representative studies.